GERMAN PRINCES ON THE BULGARIAN THRONE - Gerginova, Zlatka (Europa del Este Unida, 2021)
After the liberation from Ottoman domination in 1878 Bulgaria sought among the European princes its knyaz, who would be equally acceptable both for the Great Powers in Western Europe and for the Russian Tsar. The election falls on the 22-yearold Hessian Prince Alexander Joseph von Battenberg. His greatest merit is his role in uniting the two parts of the country. For various reasons, however, he ruled the country for only seven years and two months and was forced to abdicate in 1886. In the same year, Ferdinand Maximilian Karl Leopold Maria von Sachsen-Coburg und Gotha was unanimously elected as a knyaz, but he did not enjoy the support of Russia and the West European countries. In 1908, he declared Bulgaria's independence and proclaimed himself the Tsar of Bulgarians and led two Balkan wars. The Second Balkan War and the participation of Bulgaria in World War I are considered the worst national catastrophes. As a result, Ferdinand was forced to abdicate in favor of his son on October 3, 1918. This article seeks to answer the following questions: Why do German princes sit on the Bulgarian throne? Why are they both forced to abdicate? What are they remembered with in the history of the country? With what do they contribute to the political and economic development of the country? Why are they still of interest to historians today?